Visual Performance for Chromatic Displays - Kergoat, H.; Lovasik, J.V. (Canadian Journal of Optometry, 2026)
Video Display Uni1s (VDUs) have been incorporated in various workstations over the past few years. Their widespread use has been accompanied by many symptoms of general and visual discomfort. 0n the visual side, several studies have implicated inaccuracies in the accommdative system as the possible cause of VDU relaled visual fatigue. Further, the use of color-coded information in modern electro-optical displays may stress the focussing system even more because of the chrommic aberration presenl in the optics of the human eye. In view of the popularity of VDUs and their possible implication in user's visual fatigue, we examined lhe effect of VDU displayed colored stimuli on the visual neural and accommodarive system of the human eye. Twenty paid volunteers in a 22 to 35 year age category participated in the present study. Stimuli were presentedon a high resolution RGB monitor, as a 40 cm obseration distance and varried in color, size and degree of retinal defous. Vissually Evoked Potential (VEP) and lazer optometer techniques were used to assess visual neural and accommodative performance. Both measures isolated differential effects of these stimuli characteristics on the visual system. Results are presented and discussed as they relate to electro-optical display design.